2017
DOI: 10.1111/pedi.12493
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding metformin to insulin therapy for type 1 diabetes mellitus children: A systematic review and meta-analysis

Abstract: We aimed to assess the effectiveness of adding metformin to insulin in type 1 diabetes mellitus (T1DM) children for improving metabolic outcomes. We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) conducted on children age 6 to 19 years who are diagnosed with T1DM, and examined the effect of adding Metformin to standard insulin therapy. We performed literature searches on Ovid Midline, Ovid Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) from the date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 42 publications
2
36
0
1
Order By: Relevance
“…Our study on adjunctive metformin use in the general population with T1D reached similar conclusions to a systematic review among adolescents and a meta‐analysis of 6 RCTs . A recent meta‐analysis of 325 participants concluded that metformin reduced the TIDD and BMI but not HbA1c values in adolescents with T1D .…”
Section: Discussionsupporting
confidence: 84%
“…Our study on adjunctive metformin use in the general population with T1D reached similar conclusions to a systematic review among adolescents and a meta‐analysis of 6 RCTs . A recent meta‐analysis of 325 participants concluded that metformin reduced the TIDD and BMI but not HbA1c values in adolescents with T1D .…”
Section: Discussionsupporting
confidence: 84%
“…Reduced insulin requirement following use of high metformin doses (2550 mg/d) in patients with type 1 diabetes was also documented in a study by Pagano et al 30 Furthermore, a meta--analysis by Khalifah et al 31 showed that add -on metformin treatment reduced total daily insulin dose and BMI in children.…”
mentioning
confidence: 74%
“…16 The addition of metformin to insulin did not reduce HbA 1c levels but resulted in decreased total insulin daily dose (MD −0.16 units/kg, 95% CI −0.22 to −0.11; six studies, 325 participants) and reduced body mass index (MD −1.5kg/m 2 , 95% CI −2.5 to −0.4; four studies, 159 participants).…”
Section: About Metforminmentioning
confidence: 89%